STUDENT PERCEPTIONS OF DISTANCE LEARNING IN THE PANDEMIC ERA - Arif Widodo; Umar Umar; Ghudaifa Rasya (JURNAL EDUSCIENCE, 2022)
The purpose of this study was to determine student perceptions about learning from home or learning from home. The main problems studied are what applications are often used, the problem of quota subsidies from universities, signal constraints when studying, supervision, and the responses of parents of students when they study from home. This research will also reveal the advantages and disadvantages as well as suggestions related to learning from home that are effective and fun for students. The research method used in this research is to use quantitative research with a descriptive approach. The research subjects were students of the Mataram University PGSD Study Program semester 3. The data collection techniques were carried out by filling out a questionnaire in the form of a Google Form. The data obtained from the distribution of Google Forms to the 3rd-semester PGSD students of Mataram University showed that learning from homemade the 3rd-semester PGSD students bored and felt ineffective in learning. Students prefer to learn face-to-face because they are more effective and understand learning material more quickly. Students hope that the effectiveness of learning carried out from home online will be increased through various fun learning methods